Pertanggungjawaban Pidana Terhadap Anak Sebagai Kurir Narkoba - Janitra Jaya Negara (LPPM Universitas Ekasakti Padang, 2024)
The Law No. 35 of 2009 in Indonesia regulates and monitors the circulation of drugs. Drugs are a very dangerous drug when many layers of society abuse them. So not only the individuals who abuse the goods, but also the society as a whole is experiencing the consequences of the abuse. In implementing it, the government does not seem to be doing its best to prevent the spread of illicit drugs. As a result, not only adults but also children have become couriers in the distribution union. This research uses a legal approach. The aim of this study is to find out the legal responsibility for criminal offences as well as the legal consequences that will be received by a child who works as a drug courier.The results of this study are expected to be able to raise public awareness of the dangers of drug offenders, as well as to advise the authorities to work even harder in dealing with drug abuse in Indonesia.